Air‐Sea Heat and Momentum Fluxes in the Southern Ocean. Issue 23 (3rd December 2019) - Bharti, Vidhi; Fairall, Christopher W.; Blomquist, Byron W.; Huang, Yi; Protat, Alain; Sullivan, Peter P.; Siems, Steven T.; Manton, Michael J.
Abstract: The Clouds, Aerosols, Precipitation, Radiation, and atmospherIc Composition Over the southeRn oceaN (CAPRICORN) experiment was carried out in March–April 2016 onboard R/V Investigator studying momentum ( τ ), sensible heat ( H s ), and latent heat ( H l ) fluxes over the Australian sector of the Southern Ocean including over one cyclonic cold‐core and one anticyclonic warm‐core mesoscale oceanic eddy. The turbulence‐based flux measurements obtained with the NOAA PSD flux system employing eddy covariance (EC) and inertial dissipation (ID) methods are compared with those obtained by the Coupled Ocean‐Atmosphere Response Experiment (COARE) 3.5 bulk model, and the neutral transfer coefficients are studied. The relative uncertainty between the turbulence‐based and COARE 3.5 estimates of τ, H s, and H l are 22%, 70%, and 26%, respectively, at 1‐hr time scale over the Southern Ocean. Further, the variability in bulk fluxes is investigated with respect to oceanic eddies, precipitation events, atmospheric stability, and extratropical cyclones encountered during the voyage. The main observed variability is an increase in significant wave height or γ w (∼33%), τ (∼89%), H s (∼187%), and H l (∼79%) over the warm eddy as compared to average voyage values. During the passage of six extratropical cyclones, an increase in τ (∼62% average) and a decrease in H s (∼235%) and H l (∼79%) is noted in the warm sector, compared to prestorm conditions, but the pattern reverses behind the cold front. Key Points: COARE 3.5 bulk model gives lower mean estimates of wind stress and heat fluxes in the Southern Ocean when compared with observations The 10‐m‐neutral transfer coefficients of momentum and heat fluxes increase with wind speed >5 m/s Heat fluxes decrease in the warm sector of extratropical cyclones, but increase behind the cold front